Blended Learning Stimulating Students’ Activeness in English Teaching Learning Process - Yasminar Amaerita Telaumbanua; Benifaeri Telaumbanua; Enjel Tris Jelita Telaumbanua; Noniat Zega; Berkris opitama Lase; Ismah Yusuf Tanjung; Arni Yanti Lawolo (Departement of Mathematics Education, 2024)
Student activeness in the learning process is very important because it encourages their deeper and more meaningful engagement with the subject matter. The problem of student activeness in learning is a challenge that is often faced in the world of education, where students are less involved or actively participate in the teaching and learning process. The purpose of this study is to explore how blended learning can stimulate students' activeness especially in the English learning process to class A, sixth semester students of English education study program at University of Nias. To conduct this research, the researchers used a qualitative descriptive method with data collection techniques through interviews. The results of the data obtained about Blended learning stimulating students activeness in English teaching-learning process is Blended learning in English classes enhances students participation and activeness by utilizing online platforms and face to face group for interactive discussions and activities. With the results of this study, it is hoped that the teaching-learning methods carried out can vary and be tailored to the needs and interests of students such as this blended learning method so that students are more enthusiastic and comfortable when learning, especially when the teaching-learning process is taking place.